Kapitza light guiding in photonic mesh lattice - Muniz, Andre L. M.; Alberucci, Alessandro; Jisha, Chandroth P.; Monika, Monika; Nolte, Stefan; Morandotti, Roberto; Peschel, Ulf (Optics Letters, 2019)
We experimentally demonstrate the transverse confinement of light in the presence of a longitudinally periodic photonic potential with vanishing average. In agreement with Kapitza’s original findings in classical mechanics, we confirm that light undergoes a transverse localization due to the action of an effective potential proportional to the square of the first derivative of the potential. Experiments are performed based on (1 + 1)D synthetic dimensions realized in a fiber loop system, allowing for complete control of the transverse and longitudinal distributions of the potential.
CRIS-Team Scopus Importer:2023-04-20